2022
DOI: 10.1093/jn/nxac047
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Status of Mother-Infant Dyads from Montréal, Canada: Secondary Analyses of a Vitamin D Supplementation Trial in Breastfed Infants

Abstract: Background Most pregnant or lactating women in Canada will not meet iodine requirements without iodine supplementation. Objective To assess iodine status of 132 mother-infant pairs based on secondary analyses of a vitamin D supplementation trial in breastfed infants from Montréal, Canada. Methods Maternal iodine status was assessed using breastmilk iodine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The percentage of mothers using an iodine-containing supplement was 90% during pregnancy and 79% and 59% at 1 and 6 months of lactation, respectively. Bertinato et al [21 ▪ ] concluded that the iodine status of these mostly breastfed infants was adequate throughout infancy and these results support the recommendation that all pregnant and lactating women take a daily iodine supplement. A study from China assessed the iodine status of 556 390 schoolchildren enrolled in the 2018 National IDD Surveillance.…”
Section: Infants and Childrenmentioning
confidence: 57%
“…The percentage of mothers using an iodine-containing supplement was 90% during pregnancy and 79% and 59% at 1 and 6 months of lactation, respectively. Bertinato et al [21 ▪ ] concluded that the iodine status of these mostly breastfed infants was adequate throughout infancy and these results support the recommendation that all pregnant and lactating women take a daily iodine supplement. A study from China assessed the iodine status of 556 390 schoolchildren enrolled in the 2018 National IDD Surveillance.…”
Section: Infants and Childrenmentioning
confidence: 57%